INFORMATION TECHNOLOGY IN PROFESSIONAL EDUCATION OF MANAGERS AND ECONOMISTS - DOSTÁL, Jiří; Milan, KLEMENT; BÁRTEK, Květoslav (Trends in education, 2009)
Information technology has become a major factor in nearly every aspect of our society. The personal computer has developed into a powerful tool for gathering, manipulating, and delivering information and sophisticated databases allow us to store, collate, and access data. Networks and telecommunications technology allow delivering and retrieving information from around the world.Managers and Economists at all levels must have a better understanding of IT. Armed with this knowledge, the manager will be able to improve communication with the IT group and make more accurate business decisions.
Keywords: information technology; professional education; management; economics; business school.